1967
DOI: 10.1530/jrf.0.0140355
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in Analyses of Deoxyribonucleic Acid in Rabbit Spermatozoa, Involving Feulgen Staining (Feulgendna) and Ultraviolet Light Absorption (Uv-Dna) Measurements

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

1969
1969
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…These changes are distinct from, if additional to, presumed deterioration of the acrosome which will affect sperm penetration and, if widespread, will ultimately cause total failure offertilization. Ageing of bull spermatozoa in vitro has been shown to bring about a change in the reaction of the spermatozoa to Feulgen staining and to influence prenatal losses (Salisbury, Birge, de la Torre & Lodge, 1961 ;Salisbury, 1967) and there is evidence also that, in the rabbit, ageing in vivo of epididymal spermatozoa influences the DNA content of the spermatozoa (Bouters, Esnault, Salisbury & Ortavant, 1967). There is, thus, considerable support for the notion that the ageing of spermatozoa affects their DNA content.…”
Section: Discussionmentioning
confidence: 98%
“…These changes are distinct from, if additional to, presumed deterioration of the acrosome which will affect sperm penetration and, if widespread, will ultimately cause total failure offertilization. Ageing of bull spermatozoa in vitro has been shown to bring about a change in the reaction of the spermatozoa to Feulgen staining and to influence prenatal losses (Salisbury, Birge, de la Torre & Lodge, 1961 ;Salisbury, 1967) and there is evidence also that, in the rabbit, ageing in vivo of epididymal spermatozoa influences the DNA content of the spermatozoa (Bouters, Esnault, Salisbury & Ortavant, 1967). There is, thus, considerable support for the notion that the ageing of spermatozoa affects their DNA content.…”
Section: Discussionmentioning
confidence: 98%
“…In the presence of vas deferens obstruction, however, sperm cells may survive for many weeks (8), creating in the epididymis a highly heterogeneous environment in terms of spermatozoa age and maturity. Because there is no known correlation between physical appearance or degree of motility of the epididymal sperm cell and the level of its deterioration (9), a sperm selected for ICSI could be one that was present in the epididymis for 1 day or several weeks.…”
mentioning
confidence: 99%
“…It has been shown that the Feulgen-DNA contents of ejaculated spermatozoa are lower than those of epididymal or testicular spermatozoa (Bouters, Esnault, Salisbury & Ortavant, 1967). In the present study, all the spermatozoa were taken from the same region of the genital tract and were processed for the Feulgen reaction by methods prescribed to eliminate proportionality errors (Böhm et al, 1968).…”
mentioning
confidence: 84%